2017
DOI: 10.1007/s11064-016-2172-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical and Social Components of Enriched Environment on Astrocytes Proliferation in Rats After Cerebral Ischemia/Reperfusion Injury

Abstract: Treatment of enriched environment (EE) exerts neuroprotective effect in cerebral ischemia/reperfusion (I/R) injury. However, how the component of EE contributes to the functional recovery after brain ischemia remains unclear. Here we examined the effect of physical and social components of EE on poststroke astrocytes proliferation using an animal model of middle cerebral artery occlusion (MCAO) followed by reperfusion. Rats were divided into five groups: physical enrichment group (PE), social enrichment group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…However, how many of these effects observed in response to EE protocols rely on EE per se and how many result from physical exercise and increase of social interaction (i.e., SE) was not determined. When the effects of physical exercise and social interaction components of an EE protocol were investigated after brain ischemia/reperfusion, physical exercise and SE reduced the brain lesion (i.e., infarct volume) and increased astrocyte proliferation and brain-derived neurotrophic factor expression (57). It suggests that the physical activity component of EE might be the most important factor concerning positive results on functional, biochemical, and histological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, how many of these effects observed in response to EE protocols rely on EE per se and how many result from physical exercise and increase of social interaction (i.e., SE) was not determined. When the effects of physical exercise and social interaction components of an EE protocol were investigated after brain ischemia/reperfusion, physical exercise and SE reduced the brain lesion (i.e., infarct volume) and increased astrocyte proliferation and brain-derived neurotrophic factor expression (57). It suggests that the physical activity component of EE might be the most important factor concerning positive results on functional, biochemical, and histological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Rat models of right MCAO were established using the suture occlusion method according to established methods of the middle cerebral artery ischemia model developed by Longa et al and Chen et al 13 , 14 With room temperature maintained at 20°C–30°C, the rats were immobilized on the operating table under intraperitoneal anesthesia (1% pentobarbital sodium, 30–40 mg/kg). Following sterilization, the right common carotid artery, internal carotid artery, external carotid artery, and pterygopalatine artery were carefully isolated through a median neck incision.…”
Section: Methodsmentioning
confidence: 99%
“…Connexin-30 is elevated after EE ( 15 ) and positively regulated by neural activity ( 64 ). Previous studies have also found that physical and social components of EE treatment enhanced astrocyte proliferation and increased the expression of BDNF, which might contribute to improved neurological outcomes in stroke animals, and physical activity plays a more important role in EE treatment after cerebral ischemia/reperfusion injury ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 96%